1993
DOI: 10.1128/jvi.67.9.5419-5425.1993
|View full text |Cite
|
Sign up to set email alerts
|

Unusual regulation of expression of the herpes simplex virus DNA polymerase gene

Abstract: During herpes simplex virus infection, expression of the viral DNA polymerase (pol) gene is regulated temporally as an early (p) gene and is additionally down-regulated at late times at the level of translation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…This cannot be explained simply by the differences in basal activity of these genes, as the abundantly expressed viral genes encoding UL42 and ICP8 responded very differently to the presence of ICP27. Consistent with the work of others (2,27,89), we observed that many of the replication genes were sensitive to the status of DNA replication, but again the magnitude of that effect was not the same for all of the ␤ genes. The differing degrees to which these genes were stimulated by ICP27 did not correlate in any consistent way with the observed variations in PAA sensitivity (e.g., UL8).…”
Section: Discussionsupporting
confidence: 90%
“…This cannot be explained simply by the differences in basal activity of these genes, as the abundantly expressed viral genes encoding UL42 and ICP8 responded very differently to the presence of ICP27. Consistent with the work of others (2,27,89), we observed that many of the replication genes were sensitive to the status of DNA replication, but again the magnitude of that effect was not the same for all of the ␤ genes. The differing degrees to which these genes were stimulated by ICP27 did not correlate in any consistent way with the observed variations in PAA sensitivity (e.g., UL8).…”
Section: Discussionsupporting
confidence: 90%
“…5). The UL9 transcript is therefore an early gene product whose synthesis is reduced in the presence of PAA, as in the case of the UL30 gene, which encodes viral DNA polymerase (74).…”
Section: Fig 3 S1 Analysis Of the Ul10 Transcript (A) (Top) Locatimentioning
confidence: 99%
“…Consequently, E genes are not homogeneous with respect to activation by ICP4. Additionally, activation of some E genes, like UL9 and UL30, may be further complicated by their unusual sensitivity to the status of DNA replication (4,74). There is also the possibility that some E genes are differentially regulated in neurons; for example, the UL9 promoter has been reported to contain a cyclic AMP response element and to be differentially induced in PC12 cells (14).…”
Section: Discussionmentioning
confidence: 99%